Piperacillin/tazobactam-induced neutropenia, thrombocytopenia, and fever during treatment of a diabetic foot infection. (January 2013) - Uzun, Günalp; Önem, Yalçin; Hatipoglu, Mustafa; Turhan, Vedat; Mutluoglu, Mesut; Ay, Hakan
Abstract Piperacillin/tazobactam (PTZ) is frequently used in patients with diabetic foot infections. Herein, we report a patient who developed severe neutropenia, thrombocytopenia, and fever while receiving PTZ for a diabetic foot infection. We recommend vigilance when long-term PTZ use is planned in patients with diabetic foot infections.